PENGARUH UMK, PDRB, PMA, PMDN, DAN ANGKATAN KERJA TERHADAP PENYERAPAN TENAGA KERJA BERPENDIDIKAN RENDAH DI PROVINSI JAWA TENGAH TAHUN 2019-2024 - Azkiya Faiza Zahra; Nenik Woyanti (BISECER (Business Economic Entrepreneurship), 2026)
Central Java is a province with one of the largest labor forces in Indonesia, however, the minimum wage level established in this region remains relatively low compared to other provinces on the island of Java. This condition is further compounded by the reality that the majority of the labor force in Central Java possesses only a low educational background, namely junior high school graduates or below. On the other hand, Central Java holds considerable economic potential, as evidenced by its steadily growing Gross Regional Domestic Product (GRDP) and the presence of several strategic industrial zones that attract flows of both domestic and foreign investment. This study aims to analyze the effect of the District/City Minimum Wage (UMK), GRDP, Foreign Direct Investment (FDI), Domestic Direct Investment (DDI), and Labor Force on the absorption of low-educated workers in Central Java Province during the period 2019–2024.This study employs panel data comprising cross-sectional data from districts/cities in Central Java and time-series data spanning the years 2019 to 2024. The analytical method used is panel data regression with the Fixed Effect Model (FEM). The results indicate that UMK has a partial negative and significant effect on the absorption of low-educated workers; GRDP has a partial positive and significant effect on the absorption of low-educated workers; FDI, DDI, and the Labor Force has no significant partial effect on the absorption of low-educated workers. Simultaneously, UMK, GRDP, FDI, DDI, and Labor Force have a significant effect on the absorption of low-educated workers.